Impact of pre‐transplant depression on outcomes of allogeneic and autologous hematopoietic stem cell transplantation. Issue 10 (19th January 2017) - El‐Jawahri, Areej; Chen, Yi‐Bin; Brazauskas, Ruta; He, Naya; Lee, Stephanie J.; Knight, Jennifer M.; Majhail, Navneet; Buchbinder, David; Schears, Raquel M.; Wirk, Baldeep M.; Wood, William A.; Ahmed, Ibrahim; et al.
Abstract : BACKGROUND: To evaluate the impact of depression before autologous and allogeneic hematopoietic cell transplantation (HCT) on clinical outcomes post‐transplantation. METHODS: We analyzed data from the Center for International Blood and Marrow Transplant Research to compare outcomes after autologous (n = 3786) or allogeneic (n = 7433) HCT for adult patients with hematologic malignancies with an existing diagnosis of pre‐HCT depression requiring treatment versus those without pre‐HCT depression. Using Cox regression models, we compared overall survival (OS) between patients with or without depression. We compared the number of days alive and out of the hospital in the first 100 days post‐HCT using Poisson models. We also compared the incidence of grade 2‐4 acute and chronic graft‐versus‐host disease (GVHD) in allogeneic HCT. RESULTS: The study included 1116 (15%) patients with pre‐transplant depression and 6317 (85%) without depression who underwent allogeneic HCT between 2008 and 2012. Pre‐transplant depression was associated with lower OS (hazard ratio [HR], 1.13; 95% confidence interval [CI], 1.04‐1.23; P = 0.004) and a higher incidence of grade 2‐4 acute GVHD (HR, 1.25; 95% CI, 1.14‐1.37; P < 0.0001), but similar incidence of chronic GVHD. Pre‐transplant depression was associated with fewer days‐alive‐and‐out‐of‐the hospital (means ratio [MR] = 0.97; 95% CI, 0.95‐0.99; P = 0.004). There were 512 (13.5%) patients with Pre‐transplant depression and 3274 (86.5%) without depression who underwent autologous HCT. Pre‐transplant depression in autologous HCT was not associated with OS (HR, 1.15; 95% CI, 0.98‐1.34; P = 0.096) but was associated with fewer days alive and out of the hospital (MR, 0.98; 95% CI, 0.97‐0.99; P = 0.002). CONCLUSION: Pre‐transplant depression was associated with lower OS and higher risk of acute GVHD among allogeneic HCT recipients and fewer days alive and out of the hospital during the first 100 days after autologous and allogeneic HCT. Patients with pre‐transplant depression represent a population that is at risk for post‐transplant complications. Cancer 2017;123:1828–1838 . © 2017 American Cancer Society . Abstract : The impact of depression before hematopoietic cell transplantation (HCT) on clinical outcomes after HCT is unknown. Pre‐transplant depression is associated with lower survival and higher risk of acute graft‐versus‐host disease among allogeneic HCT recipients and longer hospital length of stay after HCT.